Bis(3-aminopyrazine-2-carboxylato-κ(2) N (1),O)diaquamanganese(II) - Zheng, Min-Yan (International Union of Crystallography, 2010)
The Mn(II) atom in the title compound, [Mn(C(5)H(4)N(3)O(2))(2)(H(2)O)(2)], exhibits an octahedral geometry comprising the two O atoms and two N atoms from two 3-aminopyrazine-2-carboxylate ligands, which act as chelating ligands, and two water molecules. An intramolecular N—H⋯O hydrogen bond occurs. In the crystal, N—H⋯O, O—H⋯N and O—H⋯O hydrogen bonds link adjacent molecules into a three-dimensional network. The molecule lies on a twofold rotation axis.